Identificaç\~ao dos principais compradores de produtos agropecuários Brasileiros - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Actually, Brazil shows expertise in production, internal supply and exports of an extended variety of agricultural products and their processed products. At the same time, several studies expose Brazil's competitive capacity in those products, and a projected increase in world demands for foods, aligned to an increasing in world population. So, in this study we tried to find a better understand about the main demander countries of Brazilian agricultural products. Data from 1997 to 2013 were employed. In terms of geographical regions European Union and South America are relevant when number of main demander countries is observed. At second, Asian countries, Middle East countries and African countries are also leader markets in demand Brazilian agricultural products, and Middle East countries are highlighted by a relatively consolidated position in buying Brazilian meat. At third, North-American countries also deserve mention. The results permitted to identify intermediate markets, which can represent potential for a better international insertion of Brazilian agricultural product.
Keywords: F14; Q11; Q17; 330; farming and castle raising; exports; Brazil